Successful third haploidentical hematopoietic stem cell transplantation after two graft failures in a pediatric patient with severe aplastic anemia: a case report with five-year follow-up - Li, Xuewei; Zhang, Wenhui; Li, Saisai; Ma, Xiaolin; Shi, Xue; Wang, Wei; Sun, Lingjie; Qiu, Kuan; Zhao, Yanxia; Zhao, Chunting; Liu, Xiaodan (Frontiers in Immunology, 2025)
BackgroundHematopoietic stem cell transplantation (HSCT) offers a potentially curative option for severe aplastic anemia (SAA). However, graft failure (GF) remains a life-threatening complication following HSCT. Haploidentical HSCT may serve as an effective salvage therapy for the treatment of GF.Case presentationThis report describes a 3-year-old girl with acquired SAA who experienced GF twice following matched unrelated donor (MUD) transplantations. Successful engraftment was ultimately achieved through a third haploidentical donor HSCT. This work was conducted in accordance with the Declaration of Helsinki and the Declaration of Istanbul.ConclusionsBased on our experience with this case, we conclude that a third HSCT with a haploidentical donor represents a viable approach to extending survival.